DETERMINATION OF THE OPTIMAL CONDITIONS FOR EXTRACTING ALPHA-AMYLASE INHIBITORS OF HUMAN SALIVA FROM FIVE MAIZE VARIETIES - Khalaf, Anwer Ahmed; Naji, Ethar Zeki (Diyala Agricultural Sciences Journal, 2018)
Alpha-amylase inhibitors were extracted from some maize varieties including Veto, Monarg Rohnaldinia, Daredh and May-70, using 0.2 M buffer solution of sodium acetate, pH 6. Inhibition of all maize cultivars towards human saliva amylase was determined by the method used. The results showed that inhibition percentages varied by different species. Rohnaldinio variety was characterized by amylase inhibition ratio of 40.26% compared to the Monarg and Veto of 23.60% and 16.47%, respectively. May-70 and Daredh showed little efficacy towards amylase. The optimal ratio for alphaamylase inhibitors extraction from maize varieties, and at different proportions including 2.5: 1, 5: 1 and 10: 1 (weight: volume), showed that the specific efficacy was the greatest when extracting the inhibitor from Rohnaldinio variety by using 1:5 (w: v) mixing proportion. The specific efficacy was 6.32 unit mg-1 protein, compared to the other varieties. Determination the optimal extraction time for alpha-amylase inhibitors from maize varieties at 1.0, 1.5 and 2.0 hours extraction time showed that the specific efficacy was the highest when the inhibitor was extracted from Rohnaldinio variety in 1.5 hour. It was 5.66 unit mg-1 protein compared to the rest of the varieties. The results also showed a pH effect on the interaction of the inhibitor with amylase saliva. The optimal pH for bindings the inhibitor from Rohnaldinia variety with amylase saliva was 6, whereas 7, 5, 8 and 6 for inhibitors from Monarg, Veto, Daredh and May-70, respectively. The optimum temperature for inhibitor activity was examined between 30 – 80 ˚C. A significant increase in the effectiveness of inhibition was shown with increasing temperature from 60 to 80 ˚C. Inhibition at 80 ˚C was 40.66% when the inhibitor from Rohnaldinia linked with amylase saliva.